Sociolinguistic Content in Training Courses: Pidgin Arabic and White Dialect for Bus Drivers - El Zahraa, Fatima; Nawawi, Mukhshon; Muttaqin, Zainal (Universitas Muhammadiyah Sumatera Barat, 2024)
This study examined a gap in the company's manual book for Indonesian bus drivers assigned to work in Saudi Arabia. The manual book used formal Arabic vocabulary about bus parts, occupational safety, and traffic signs, while foreign workers from India, Pakistan, and Bangladesh frequently communicated in simplified Arabic. This discrepancy highlights the need to align training courses with the practical demands of daily interaction. The study employed a qualitative descriptive content analysis approach. The findings confirm Canagarajah's work on the importance of sociolinguistic competence in transnational work environments, Duggan's focus on the necessity of sociolinguistic awareness for migrants, and Kött and Vogl's research on the role native speakers play in acquiring hybrid Arabic. It supports Ubalde et al.'s findings on the impact of interethnic contact on language learning and aligns with Al-Rojaie's analysis of dialectal variations in Saudi Arabia. Furthermore, it agrees with Al-Mutayri and As-Susuwah's studies on pidgin Arabic. The study concludes the importance of equipping bus drivers with language variation in real-world communication and recommends incorporating sociolinguistic content into training courses to address multicultural work environment challenges.